Water Extract of Onion Catalyst: A Sustainable Approach for the Synthesis of 4-Substituted 1,5-Benzodiazepine Derivatives via an In Situ Generated Enaminones - Selvaraj, Loganathan; Eswaran, Rajendran; Natesan, Vennila K.; Muthu, Seenivasa Perumal (Current Organocatalysis, 2024)
Background: A simple, convenient and environmentally benign green protocol has been developed for the one-pot synthesis of 4-substituted-1,5-benzodiazepines through three-component reaction of 1,2-diamine, 1,3-cyclic diketone with an aldehyde catalyzed by water extract of onion. The reaction conditions were optimized and the scope of the reaction was extended to various 1,2- diamines, 1,3-cyclic diketones and aldehydes. The main advantages of this method are good to excellent yields, easy workup, simple experimental procedure, and an ability to tolerate a variety of functional groups which gives cost-effective as well as green rewards. The structure of compound 5f was confirmed by single crystal X-ray analysis. Objective: A methodology developed for the synthesizing of 4-substituted 1,5-Benzodiazepine derivatives via enaminones intermediates using 1,2-diamine, 1,3-cyclic diketone and aldehyde in environmentally friendly ethanol as medium. Methods: As a more environmentally friendly catalyst for producing products containing benzodiazepines using aqueous extract of onion. The devised method was proven reliable, non-toxic and greener solvent with quick work-up to produce the intended product. Results: Here, using a one-pot, three-component reaction with a dimedone, 1,2-diamine and range of aldehyde while using water extract of onion as a catalyst. The acquired experimental results showed that the employed synthesis methodology is a straightforward procedure that offers various benefits, including sustainability, easy separtion from the reaction medium. Conclusion: We have developed a sustainble approach for synthesizing benzodiazepine from radily available precursors under mild reaction conditions.
Keywords: enaminone